Penanggulangan Kasus Gizi Kurang Dengan Intervensi Demo Masak Di Desa Rugemuk Kec. Pantai Labu - Tanjung, Nadya Ulfa (FKM UIN Sumatera Utara Medan, 2023)
Medan City is a part of North Sumatra Province. The prevalence of undernutrition and malnutrition in Medan City in 2013 was 19.3%, consisting of 4.2% of malnutrition and 15.1% of undernourished. This prevalence rate is close to the national figure, which is 19.6%. Meanwhile, based on the 2015 MDG's target, the prevalence of malnutrition and under-five children is 15.5%, this prevalence rate is included in the high category. The methods used in this community service are counseling, demonstrations and measurement of nutritional status. The result of the service is that counseling is carried out 3 times. It was carried out once at the Puskesmas Rugemuk Pantai Labu District. In the cooking demonstration, the material provided is the use of abundant ingredients from Rugemuk Village, such as sea fish, shrimp, squid into various foods that have high nutritional value and are of sale value. The processed food is in the form of fish nuggets. From the results of the intervention and observations made, there are several children in Rugemuk Village whose nutritional status is lacking. The conclusion in this service is that the intervention activities carried out to solve the problem are counseling to the community as well as data collection and measurement of height and weight in children. All activities went well and smoothly, counseling to the community as well as data collection and measurement of height and weight for children.